Distribution pattern and influencing factors for the microplastics in continental shelf, slope, and deep-sea surface sediments from the South China Sea. (15th September 2022) - Ding, Yongcheng; Zou, Xinqing; Chen, Hongyu; Yuan, Feng; Liao, Qihang; Feng, Ziyue; Fan, Qinya; Wang, Ying; Fu, Guanghe; Yu, Wenwen
Abstract: Marine microplastic pollution has become a major global concern in recent years and the fate of microplastics in the ocean is a hot issue of research. We investigated microplastic pollution in surface sediments in the northern South China Sea to explore its distribution characteristics and influencing factors across the continental shelf, continental slope, and deep-sea environments. It was found that the microplastic abundance of surface sediments was 130.56 ± 40.48 items/kg. The average abundance of microplastics in all three topographic areas gradually decreased with increasing distance offshore. However, the differences in microplastic diversity indices between the three areas were not significant and were higher than those in other seas of the world, indicating that the waters of the northern South China Sea are rich in microplastics from complex sources, with more pollution input channels. In the continental shelf, fibrous and low density microplastics accounted for the largest amount, with a low degree of microplastic aging, and were mostly transported by suspended-load. These microplastics were mainly influenced by human activities. In the deep sea, microplastics with higher density were the most abundant and the number of fibrous microplastics was fewer, while the average size was larger, mainly influenced by the bottom currents. These microplastics underwent long-term bedload transport. In the continental slope, the main factors affecting the distribution of microplastics were more complex. In addition to pollution by human activities, the slope also receives microplastic materials carried by bottom currents; therefore, the composition of microplastics in the slope combines those characteristics of microplastics in both the continental shelf and deep-sea areas. The findings of this study indicate that the South China Sea is affected by complex pollution sources under the dual effects of human activities and natural conditions; in particular, the pollution situation in the deep-sea area needs extensive attention. Graphical abstract: Image 1 Highlights: Distribution of microplastic and characteristics from the northern SCS are reported. MPs distribution is mainly affected by human activities and bottom currents. Continental shelf has higher abundance than continental slope and deep-sea areas. Deep-sea areas potentially pool large amounts of microplastics. Prominent MDI in northern SCS reflects the diversity of pollution input channels.